Características físicas e mecânicas de materiais resinosos utilizados para restauração de dentes tratados endodonticamente usando dois protocolos de fotoativação - Mendoza, Lilibeth Carola Leyton (2023)
The resin-based material type and the light activation protocol can influence the mechanical properties of the post cementation and core reconstruction for restoring endodontic treated teeth. This study evaluated the mechanical properties influenced by immediate or 5-minutes delayed light activation of different resin-based materials to cement fiberglass post (dual-cure resin cements or dual-cure resin-core) and to build the core (bulk-resin RBCs or dual-cure resin-core). Nine resin-based materials were tested: 4 dual-cure resin-core: Allcem Core, FGM; LuxaCore Z, DMG; Rebilda DC, VOCO; Clearfil DC Core Plus, Kuraray; 3 dual-cure resin cements: RelyX Universal, 3M Oral Care; RelyX U200, 3M Oral Care; Allcem Dual, FGM; and 2 bulk-fill resin-based composites (RBCs): Opus Bulk Fill APS, FGM; and Filtek One Bulk Fill, 3M Oral Care. The dual-cure materials were light-activated using two protocols: immediate and 5minutes delayed. The post-gel shrinkage (Shr, %), flexural strength (FS, MPa), elastic modulus (E, MPa), diametral tensile strength (DTS, MPa), compressive strength (CS, MPa), Knoop hardness (KH, N/mm2), degree of conversion (DC, %), depth of cure (DoC, mm), thermogravimetric analysis (TGA, % filler content), radiodensity, were measured. Scanning electric microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) were used to evaluate the filler content morphology. The residue of the materials that remained into the automix tip was weighted. Shr, TGA, FS, E, DTS, CS, DoC, and radiopacity data were submitted to 2-way ANOVA; KH and DC were submitted to 2-way repeated measures ANOVA followed by Tukey test (α= .05). Delayed light activation reduced significantly the Shr for all dual-cure materials (p < .001). Increasing depth significantly reduced the KH values for all materials (p < .001). Bulk-fill RBCs and resin-core materials had higher KH values than dual-cure resin cements (p < .001). Delayed light activation maintained or increased the KH for dual-cure materials. Bulk-fill RBCs had significantly lower DoC than dual-cure materials (p < .001). Delayed light activation reduced significantly the Shr values and had no negative or improvement effect on the tested mechanical properties. Dual-cure resin-based materials had higher DoC than bulk-fill RBCs. Resin-core materials had higher KH values than dual-cure resin cements and similar mechanical properties of RBCs.